Síntese e caracterização de filmes nanocompósitos de óxido de grafeno reduzido, nanotubos de carbono e azul da Prússia para a determinação de peróxido de hidrogênio e cloro ativo - Silva, Samuel Carlos (2021)
In this work is proposed an entirely chemical synthesis of a reduced graphene oxide (rGO), carbon nanotubes (CNT) and Prussian blue (PB) transparent self-assembly film through the interfacial method. The carbon nanostructures previously dispersed in toluene were added to solutions containing the precursor reagents (FeSO4, K3[Fe(CN)6 ). Morphological and particle size control of the Prussian blue nanoparticles were achieved by a slow Fe2+ release mechanism in reaction medium using sodium citrate as complexing agent and controlled acid addition. Spectroscopic results confirmed the presence of both PB and carbon nanostructures in the film. Scanning electron microscopy images validated the interaction between the nanomaterials with changes in the PB nanoparticles morphology and particle size due to the support of the carbon nanostructures and the citrate/acid mechanism utilized. The enhanced Prussian blue electrochemical stability in neutral and alkaline medium due to carbon structures interaction was observed through voltammetric measurements. An electrochemical sensor for H2O2 and free chlorine using amperometric detection was proposed. The determination was performed with batch injection analysis (BIA) system in a 3D printed electrochemical cell. The modified electrode showed good analytical performance with correlation coefficient of 0.999/0.997, linear range of 50-1000 µmol L-1, limit of detection values of 8.7/2.1 µmol L-1 and experimental variation of 5.1/0.3% for H2O2 and free chlorine, respectively. To demonstrate the sensor viability in samples of commercial products, H2O2 was determined in a body hair lightening lotion and free chlorine was determined in tap water samples, with excellent recovery results of 110/99%, respectively.